Providing Feedback: English language teachers' practices in secondary level - Pradhan, Sweety; Ghimire, Nani Babu (Siddhajyoti Interdisciplinary Journal, 2022)
Feedback is one of the key factors in language learning which may encourage or discourage learners in order to overcome mistakes and errors. The aim of the study is to examine the secondary level English teacher's feedback practices on student's work and student's perception to the type of feedback they receive. This research is based on the response to questionnaire and checklist from forty students of secondary level and ten English teachers at different secondary schools. Major findings of the study include that for the correction work, most of the teachers frequently follow teacher correction and some of the teachers frequently follow self-correction techniques. Ninety per cent of the students got motivated by positive especially teacher's praise and encouragement. The study shows most of the students need teacher's guidance in correcting their mistakes while learning English where teachers sometimes preferred their students to realize the mistakes themselves.